Effects of fatigue on the neuromuscular capacity of professional soccer players - Moreira, P. V.S.; Gonçalves, M.; Crozara, L. F.; Castro, A.; Neto, A. F.; Goethel, M. F.; Cardozo, A. C. (Isokinetics and Exercise Science, 2015)
BACKGROUND: High-speed exercise is an essential training component to prepare athletes for competition. To date correlations between anthropometry and high-speed exercise performance are mixed. OBJECTIVE: To assess anthropometry as a correlate to performance from workouts comprised exclusively of tonic or phasic repetitions done on a high-speed resistive exercise device (Impulse Training Systems; Newnan, GA). METHODS: Male athletes (n = 31) did two workouts that involved performance of a standing unilateral rowing motion with their left arm for two 60-second sets. Each workout was comprised solely of tonic or phasic repetitions. Anthropometric measurements included: height, mass, body fat percentage, shoulder width, upper and lower arm lengths as well as torso length. Mean force and total work values from each type of workout served as criterion variables. RESULTS: Anthropometry predicted significant amounts of variance for both mean force and total work values (r2 ~ 0.21) from tonic workouts. However anthropometry failed to predict a significant amount of performance variance from phasic workouts. CONCLUSIONS: Anthropometry acts as a better correlate to high-speed resistive exercise performance for repetitions that do not terminate with impact forces and are inherently less ballistic, as the latter likely utilizes less momentum. ABSTRACT FROM AUTHOR